Weathering indicators from biotic and organic amendments in rock powder column experiments - Rieder, Lukas; Hagens, Mathilde; Poetra, Reinaldy P; Vidal, Alix; Calogiuri, Tullia; Neubeck, Anna; Singh, Abhijeet; Corbett, Thomas; Niron, Harun; Vicca, Sara; Vlaeminck, Siegfried E; Janssens, Iris; et al. (PANGAEA, 2025)
The dataset comprises measurements of weathering indicators in relation to the addition of microorganisms, enzymes, earthworms, and organic matter to different rock powders. Data was collected within the BAM! project (Bio-Accelerated Mineral Weathering), which investigates the potential of soil biota and organic inputs to accelerate mineral weathering processes for carbon sequestration. Experimental data were obtained from 4 rounds of column experiments conducted between March 2022 and March 2023 at Wageningen University & Research. Treatments included combinations with and without biotic and organic amendments, allowing for comparative assessment of their influence on mineral weathering. The dataset contains measurements of key weathering indicators, including dissolved organic carbon, dissolved inorganic carbon, total alkalinity, pH, electrical conductivity, major cations and anions, as well as selected trace elements.
Keywords: Artificial system; Column experiment; Controlled Environment; dissolution experiment; Earthworms; enhanced weathering; enzymes; groundwater; microorganisms; mineral weathering; organic matter; organic matter degradation; Organo-mineral mixture; weathering; Weathering indicators